SISTEM INFORMASI HONORARIUM BERBASIS WEB DI DINAS PEMAKAMAN DAN PERTAMANAN KOTA BANDUNG - Sugiyanto Ikhsan; Gunardi Gunardi; Adri Arisena (IKOPIN, 2019)
This research was aimed to know: (1) Procedure of honorarium’s payment at Dinas Pemakaman dan Pertamanan Bandung, (2) Solving the problem that appear to the reporting process, (3) Development of Honorarium Information System Design. This research use the waterfall design method and observation technique with through literature research that related to set of problems. The problems that are found are the less effective for recording because it is still using Microsoft Office Excel 2007. The result of the research: (1) Make a standardized procedures of honorarium’s payment, (2) Problems solved in the report, (3) Created an adequate of Information System Honorarium. Based on the explanation above, then , it can be concluded that the information systems honorarium can reduce the problem that appear to the reporting process. There are some suggestions: (1) Provide special training to employees, (2) Create a programs better in the future, (3) Produce of Human Resources that can be responsible for system maintenance